Pristop k izdelavi spletnega slovarja ARTES francosko-slovenskega strokovnega jezika - Vaupot, Sonia (Slavistična revija, 2022)
Slovenia’s accession to the European Union created a need for bilingual and multilingual lexical and terminological resources, including for the French-Slovenian language pair. This article describes the development of the French-Slovenian online terminological and phraseological dictionary ARTES. The genesis and structure of the dictionary are explained, as well as the pedagogical approach to the creation of the database. The results obtained with regard to the field of Karst studies and generic collocations are presented on the basis of the data sets.
Keywords: francoščina; frazeologija; French; Karst; Kras; online dictionary; phraseology; Slovene; slovenščina; specialised language; spletni slovar; strokovni jezik; terminologija; terminology